2021
DOI: 10.3390/ijms22094546
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Development Ubiquitin-Specific Peptidase (USP) Inhibitors

Abstract: Ubiquitylation and deubiquitylation are reversible protein post-translational modification (PTM) processes involving the regulation of protein degradation under physiological conditions. Loss of balance in this regulatory system can lead to a wide range of diseases, such as cancer and inflammation. As the main members of the deubiquitinases (DUBs) family, ubiquitin-specific peptidases (USPs) are closely related to biological processes through a variety of molecular signaling pathways, including DNA damage repa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 166 publications
(162 reference statements)
1
58
0
Order By: Relevance
“…Studies carried out in the past few decades have revealed the critical roles of DUBs in various diseases, especially cancer, providing sufficient evidence for the development of these molecules as potential pharmaceutical targets, and considerable progress has been made in the development of inhibitors against several DUBs such as USP1 and USP7 ( Harrigan et al, 2018 ; Chen S. et al, 2021 ; Nininahazwe et al, 2021 ). Nevertheless, progress in the development of USP21 inhibitors remains limited.…”
Section: Inhibitors Of Usp21mentioning
confidence: 99%
“…Studies carried out in the past few decades have revealed the critical roles of DUBs in various diseases, especially cancer, providing sufficient evidence for the development of these molecules as potential pharmaceutical targets, and considerable progress has been made in the development of inhibitors against several DUBs such as USP1 and USP7 ( Harrigan et al, 2018 ; Chen S. et al, 2021 ; Nininahazwe et al, 2021 ). Nevertheless, progress in the development of USP21 inhibitors remains limited.…”
Section: Inhibitors Of Usp21mentioning
confidence: 99%
“…Studies have shown that USPs (USP2a, USP4, USP9X, USP15, and USP26) are involved in the regulation of TGF-β signaling pathways in various cancers ( 17 ). For example, USP9X can control the monoubiquitination of SMAD4 to regulate TGF-β-mediated cancer metastasis ( 101 ).…”
Section: Important Signaling Pathways In Pc Tmementioning
confidence: 99%
“…The K48 and K63 chains are the most studied ubiquitin chain linkages that guide the expression of substrate proteins. The K48 ubiquitin chain has been shown to play an important role in ATP-dependent proteasomal degradation ( 16 ), while the K63 ubiquitin chain is mainly involved in the modification of protein location and function ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…funding acquisition: X.W. All authors have read and agreed to the published version of the manuscript [128,138] Author Contributions: Conceptualization, X.W. and H.Z.…”
Section: Conflicts Of Interestmentioning
confidence: 99%